PLTP activity is a risk factor for subsequent cardiovascular events in CAD patients under statin therapy: the AtheroGene Study - Axel Schlitt; Stefan Blankenberg; Christoph Bickel; Karl J. Lackner; Gunnar H. Heine; Michael Buerke; Karl Werdan; Lars Maegdefessel; Uwe Raaz; Hans J. Rupprecht; Thomas Munzel; Xian-Cheng Jiang (Journal of Lipid Research, 2009)
Phospholipid transferprotein (PLTP) mediates both net transfer and exchange of phospholipids between different lipoproteins. Although many studies have investigated the role of PLTP in atherogenesis, the role of PLTP in atherosclerotic diseases is unclear. We investigated the association of serum PLTP activity with the incidence of a combined endpoint (myocardial infarction and cardiovascular death) and its relation to other markers of atherosclerosis in 1,085 patients with angiographically documented coronary artery disease (CAD). In the median follow-up of 5.1 years, 156 patients had suffered from the combined endpoint of myocardial infarction or cardiovascular death including 47 of 395 patients who were on statins at baseline. In Kaplan-Meyer analyses serum PLTP activity was not associated with the combined endpoint in all patients. However, in the subgroup of patients receiving statins at baseline, PLTP was shown to be a significant predictor of cardiovascular outcome (P = 0.019), and this also remained stable in univariate (P = 0.027) and multivariate cox regression analyses (P = 0.041) including potential confounders (classical risk factors, HDL cholesterol (HDL-C), and others). We showed in our study that, under statin treatment, high plasma PLTP activity was related to fatal and nonfatal cardiovascular events in CAD patients.